EVALUASI PENGELOLAAN MP-ASI LOKAL DAN PENGARUHNYA TERHADAP PENINGKATAN BERAT BADAN DAN STATUS GIZI BALITA USIA 6-24 BULAN DI PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS - Dardjito, Endo; Suryanto, Suryanto (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
The Evaluation of Management MP-ASI Local and The Influence Towards Body Heavy Enchanced and Children Under Five Nutrient Status Age 6-24 Months In Banyumas Regency. Background: Nutrient problem besides problem sindroma tight poverty with also concern behaviour change problem less support in alive pattern wells. In baby and child, nutrient deficit will evoke growth disturbance and development when not be overcome according to early continue up to adult. MP-ASI that given should made from cheap food stuff and easy goat local region. The wacthfullness aims to detect about management MP-ASI local and the influence toward age child body heavy enchanced 6 - 24 months. Objectives: This study aims to evaluate the local MP-ASI management and effect on growth of children aged 6 to 24 months in the Health Center of South Purwokerto, Banyumas. Methods: Study design is cohort retrospective. Total samples are 35 children under two years old (6-24 months) at Community Health Centre South Purwokerto. Samples has get local supplementary feeding (MP-ASI) in 2007. Data collected was socio economic household, weight of children and supplementary feeding management by interview with mother and report from Community Health Centre. Data analysis is descriptive. Nutritional status is base on Z score WHO-NCHS. Results: The local supplementary feeding (MP-ASI local) that given disagrees with guides from Health Department. A large of samples (42.9%) has given raw food stuff, 11.4% has give money and others 45.7%. There influence used MP-ASI local with body heavy enchanced especially 1 in 2 and 3 and the gift influence MP ASI local towards nutrient status enchanced especially in to 3, although low the connection with value p 0.032 and association value 0.289. Conclusions: Alternative nutrient problem in family necessary with approach multisector among others well being sector, industrial, agricultures and others. Necessary family enableness movement existence so that can increase economy social level and can run family function in especially well being area. Gift MP-ASI that done according to adekuat the nutrient value in target as according to age and instruction that determined can increase growth and children under five development in an optimal fashion. Keywords: colleague food, heavy body, nutrient status